2013
DOI: 10.1007/s12070-013-0624-z
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of Medullary Thyroid Carcinoma

Abstract: Medullary thyroid carcinoma (MTC) is extremely uncommon having varied presentations & their prognosis is not exactly known; but as MTC is an aggressive tumor hence it needs to be documented in literature to help to know the behaviour of this variant. We report a rare presentation of medullary carcinoma of thyroid in a 48 years old man who presented with huge swelling at left side of neck extending from parotid to supraclavicular region with normal-sized thyroid gland of long duration. FNAC & incision HPE of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…According to a previous report [18], PTH immunostaining is frequently weak or shows focal positivity, particularly in adenoma, carcinoma, and oxyphilic cells. Chromogranin A is also expressed in medullary carcinoma of the thyroid [19]. Ordóñez has reported that GATA-3 nuclear expression was revealed by immunohistochemistry in all hyperplastic parathyroid glands, as well as parathyroid adenomas and carcinomas [7].…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous report [18], PTH immunostaining is frequently weak or shows focal positivity, particularly in adenoma, carcinoma, and oxyphilic cells. Chromogranin A is also expressed in medullary carcinoma of the thyroid [19]. Ordóñez has reported that GATA-3 nuclear expression was revealed by immunohistochemistry in all hyperplastic parathyroid glands, as well as parathyroid adenomas and carcinomas [7].…”
Section: Discussionmentioning
confidence: 99%
“…Single soft tissue metastasis of MTC is extremely rare, although several case series show an unusual presentation of distant metastases of MTC [68]. We searched the PubMed database using the keywords “medullary thyroid carcinoma or MTC”, “cutaneous or subcutaneous metastasis,” and “soft tissue metastasis.” We found several cases reports of cutaneous metastasis of MTC [7, 8].…”
Section: Discussionmentioning
confidence: 99%
“…1 If the tumor is confined to the thyroid, without nodal or distant metastasis, then it is associated with prolonged survival. 1 Treatment is primarily surgical and prognosis depends upon the stage and completeness of excision.…”
Section: On Certain Occasions It Is Difficult To Differentiate Mtc Andmentioning
confidence: 99%
“…Medullary carcinoma of thyroid (MTC) is an uncommon malignant epithelial neoplasm showing parafollicular cell (C cell) differentiation. MTC has the potential to mimic other thyroid tumors morphologically . Cytological diagnosis is often difficult .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation